The Emerging Role of Ionic Liquid-Based Approaches for Enhanced Skin Permeation of Bioactive Molecules: A Snapshot of the Past Couple of Years - Ana Gomes (MDPI AG, 2021)
Topical and transdermal delivery systems are of undeniable significance and ubiquity in healthcare, to facilitate the delivery of active pharmaceutical ingredients, respectively, onto or across the skin to enter systemic circulation. From ancient ointments and potions to modern micro/nanotechnological devices, a variety of approaches has been explored over the ages to improve the skin permeation of diverse medicines and cosmetics. Amongst the latest investigational dermal permeation enhancers, ionic liquids have been gaining momentum, and recent years have been prolific in this regard. As such, this review offers an outline of current methods for enhancing percutaneous permeation, highlighting selected reports where ionic liquid-based approaches have been investigated for this purpose. Future perspectives on use of ionic liquids for topical delivery of bioactive peptides are also presented.